2009
DOI: 10.1111/j.1532-950x.2009.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Feline Ilial Fractures: Assessment of Screw Loosening and Pelvic Canal Narrowing After Lateral Plating

Abstract: Pelvic canal narrowing >45% is associated with a high risk of recurrent constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(120 citation statements)
references
References 16 publications
7
111
2
Order By: Relevance
“…Both single and double locking plate constructs were associated with statistically significantly less screw loosening than were nonlocking plates. Loose screws were detected in 50% of the fractures plated with DCP, which is similar to rates reported by others for nonlocking devices . Screw loosening did not occur in cats with 1 or 2 LPS, except for 1 screw that was placed in the fracture line.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Both single and double locking plate constructs were associated with statistically significantly less screw loosening than were nonlocking plates. Loose screws were detected in 50% of the fractures plated with DCP, which is similar to rates reported by others for nonlocking devices . Screw loosening did not occur in cats with 1 or 2 LPS, except for 1 screw that was placed in the fracture line.…”
Section: Discussionsupporting
confidence: 87%
“…The narrow width of the ilial wing and body, which allows only limited bone purchase, has been suggested as a predisposing factor for the high rate of screw loosening associated with lateral plating of the ilium . In a recent study in cats it was demonstrated that screws have less than 80% bone purchase per unit length of ilium compared to dogs . Poor screw bone purchase may explain the high rate of screw loosening in lateral plating of the feline ilium …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations